Valorization of African Elemi Shell Waste Into Porous Hydrochar Via Hydrothermal Carbonization for Carbon Capture Applications - Calistus Princewill Odeh; Chibuzo Ndubuisi Okoye; Augustine Uzodinma Madumere; Sunday Chimezie Anyaora (Action Research Journal Indonesia (ARJI), 2026)
Because of the world's rapid expansion, more biomass waste is being produced as a result of increased agricultural and industrial processing activities. It is imperative that these waste materials be transformed into a product that can stimulate the economy and create wealth. In this task, African elemi shells are hydrothermally carbonized to produce hydro-char using locally sourced biomass waste. In order to create a hydro-char of higher quality for the adsorbent, the Response Surface Method was used to design the experiment. A design expert chose the parameters based on temperature, residence time, and W-B ratio. The combination of 220 °C reaction temperature, 90 minutes’ residence time, and 12 grams W-B ratio produced the hydro-char with the largest specific surface area (976.3 m2/g) and pore volume (2.25 cc/g). The combination of 180 °C reaction temperature, 30 minutes’ residence time, and 8 grams’ water-biomass ratio produced the hydro-char with the smallest specific surface area and pore volume (156.2 m2g-1 and 0.13 cc/g, respectively). According to the findings, the hydrochar made from HTC of African Elemi Shell at reaction temperatures of 2180C, residence times of 86 minutes, and a water-to-biomass ratio of 10.3 grams can be used as an adsorbent for CO2 capture.